Analysis of Protein Content in Moringa Leaves (Moringa oleifera) and Katuk (Sauropus androgynus) as an Alternative Plant-Based Protein - Maulina, Tiara; Anggraeni, Egi Syahrah; Pratama, Kiki Putri Septya; Jannah, Miftahul; Masruhim, Muhammad Amir (Universitas Pendidikan Mandalika, 2025)
Indonesia has many extraordinary biological resources, including flora that have great potential to function as a source of vegetable protein, such as Moringa oleifera and Sauropus androgynus. Humans need protein because it is a macromolecule that does many things for life systems, and is needed for tissue replacement and energy supply. Protein functions as a catalyst, transports molecules such as oxygen, supports the immune system, and transmits nerve impulses. The focus of this study was the protein content in moringa leaves (Moringa oleifera) and katuk leaves (Sauropus androgynus) in the shoots, young, and old parts. The moringa leaf samples examined showed a protein content of 22.24% in the shoots, 2.992% in the young leaves, and 4.272% in the old leaves. Meanwhile, fresh katuk leaves showed a protein content of 3.898% for the shoots, 4.767% for the young leaves, and 5.127% for the old leaves. The method used was the Kjeldahl method, namely the process of destruction, distillation, and titration used to measure protein content. The results of the study showed that moringa leaves, especially the shoots, have a higher protein content compared to katuk leaves, indicating that moringa leaves can function as an important source of vegetable protein. This study aims to measure and compare the protein levels in the top, young and old leaves of the two plants in fresh condition, in order to provide a more accurate picture of the nutritional potential of each part of the leaf and its contribution to the diversification of vegetable protein sources.